Pelatihan Motivasi Kewirausahaan Berbasis Koperasi Di Pasar Johar Semarang - Pratamada Bintang Suhbrastha; Givanda Eka Dhea Fadhilah; Wahyu Karminita; Ahmad Faruq; Riyanni Cinta Sari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This activity aims to explore the effectiveness of cooperative-based entrepreneurial motivation training in improving the performance and sustainability of Micro, Small, and Medium Enterprises (MSMEs), by providing the knowledge, skills, and attitudes needed to become a successful entrepreneur. Pasar Johar Semarang SME entrepreneurs face various challenges in running cooperative-based entrepreneurship. It is often difficult to reach a wider market because of limited access to strategic distribution locations that inhibit the potential for business expansion. Through this training, participants are expected to learn about the benefits of being a member of a cooperative, such as access to capital, training, and business networks. will provide training on a range of business skills essential to SMEs, such as financial management, marketing, and product development. The participants will learn how to manage their business more effectively and efficiently. By presenting speakers from UMKM Center Central Java, participants as SME entrepreneurs in Pasar Johar can ask questions directly related to problems that are often encountered in the field not only about cooperative problems but other complaints ranging from existing regulations, trade permits from orders, and even procedures for getting help from the government. These efforts are expected to help pasar Johar Semarang SME partners in developing cooperative-based entrepreneurship in a sustainable manner.